Epigenetics or “beyond Genetics” Part II (Academic Journal of Internal Affairs, 2025)
Aim: The authors of the two-part study describe a recently emerging scientific field, epigenetics, based on published literature data, and in this second part, they present results achieved in the domain of forensic sciences – genetics and ridgeology.Methodology: The study reviews and synthesizes the articles on the epigenetic basis of fingerprint development and DNA-based biological age estimation. It also describes research results on identical twins.Findings: Surprisingly little is known about the factors that influence the pattern formed by the dermal ridges. Related individuals have more similar fingerprints than unrelated individuals, suggesting that the formation of dermal ridge system is genetically controlled and that the size, shape, and spacing of the ridges are also influenced by genetic factors. In the formation process, small random events influence the formation of individual minutiae, which are therefore epigenetic effects. All external and internal environmental factors can cause chemical modifications in our genes, turn them on or off over time. DNA methylation patterns can be used to determine biological age (epigenetic clock). Knowing how old someone is at the epigenetic level can not only provide insight into an individual's biological clock but can also provide important investigative data in law enforcement. Age estimation is a critical aspect of reconstructing a biological profile in forensic science. Epigenetic clocks, which analyze DNA sections that undergo hypermethylation or hypomethylation as individuals age, are the best predictive models of age.Value: The study provides comprehensive findings of the molecular background of epigenetic inheritance through published literature studies on the development of dermal ridges and DNA age estimation and offers actionable suggestions for slowing down the epigenetic clock.
Keywords: genetics, epigenetics, gene expression, ridgeology